Edizioni italiane dei libros de caballerías nella Biblioteca Nacional de Madrid. Ciclo di Amadís de Gaula. - Body Morera, Enrique; Foti, Vittoria (Cuadernos de Filología Italiana, 2007)
In the Biblioteca Nacional de Madrid Enrique Body Morera is carrying out the demanding task of cataloguing the Italian ancient collection. Among the various books that are classified as anonymous the compact group of fifteenth and sixteenth century books belonging to the Amadís de Gaula series stands out. These translations and rewritings form an interesting chapter that deserves to be studied in the context of the fifteenth century fiction and cultural relations between Italy and Spain.